AI-INFLUENCERS AND ARTIFICIAL INTELLIGENCE IN MARKETING (Development Service Industry Management, 2025)
The theoretical foundations of influencers’ activities and their social impact are presented. Theoretical foundations of functioning and distinctive features of AI influencers are generalized. Analysis of existing research of AI influencers’ activities in Ukraine has been conducted.A brief evolution of influencers in the 20th and 21st centuries is shown, with an emphasis on creation and functioning of AI influencers. It is demonstrated that virtual characters have evolved from symbolic entertainment figures to fully-fledged communication agents capable of influencing consumer behavior in real marketing environment. Chronological stages in the evolution of AI influencers are outlined — from early prerequisites and experimental media to commercial influencers and modern virtual personalities. The main characteristics of an AI influencer are identified and described, including features defined by their virtual nature, socio-psychological characteristics, technological traits, marketing advantages, and communicative features.A comparison between AI influencers and real-life bloggers based on audience size has been conducted, showing that AI influencers have audiences currently comparable to those of human influencers. Key research metrics for comparing AI influencers and human influencers are proposed and described, including the integral account quality index, engagement rate, percentage of real followers, percentage of mass followers, follower growth, and posting frequency.Using these key metrics, a comparison between human influencers and AI influencers was carried out. It is substantiated that AI influencers are not inferior, in general, to human influencers based on the selected characteristics for analysis and even outperform them in certain aspects.The key advantages of AI influencers are identified, including consistent control, visual quality, scalability, audience quality, reputation safety, content automation, and adaptability to trends.
Keywords: marketing; influencer; AI influencer; artificial intelligence; evolution; characteristics; key research metrics